Germanium recovery from Fargo Oil's Lang Bay property - P. B. Queneau; Peter V. Avotins; Lauch F. Farris (Canadian Institute of Mining, Metallurgy and Petroleum, 1986)
"The Lang Bay germanium property is a carbonaceous sandstone deposit outcropping near the Pacific coast, 100 km north of Vancouver. The germanium-bearing seams are up to 5 m thick. Where one such seam outcrops, it averages 50 to 60 g Ge/tonne. Drill core analyses have shown considerably greater concentrations of germanium at depth. Additional drilling to establish continuity and grade of the germanium-b earing strata is scheduled for 1986. The germanium occurs in association with lignite, which makes up 1 to 2% of the seam. American Cyanamid Company engineers have developed a proprietary flotation reagent effective for concentrating the germanium rich vitrain portion of the Lang Bay lignite. Ongoing laboratory studies are developing procedures for further upgrading and refining of this germanium. This paper outlines progress made by Fargo Oil Corporation on Lang Bay geology, reserve estimation, mine planning, ore dressing, refining, and economic evaluation.IntroductionIn 1871, Mendeleyev specula ted on the properties of a ""missing"" element between silico n and tin on the periodic table. The discovery of germanium fifteen years later proved the Mendeleyev predictions to be remarkably accurate. Almo half a century later, the pioneering work of McCutcheon of Eagle-Picher led to production of germanium dioxide from Oklahoma zinc smelting residues. Demand for the element surged due to development of the Ge02 diode rectifier during World War II, followed by development of the transistor in 1947. The chief commercial sources for germanium during the following two decades were the Cu-Zn mines in the Congo and the Zn-Cu-Pb mines of Tsumeb in Southwest Africa. The germanium was chemically combined in complex Cu-Fe sulphides (germanite and renierite), from which the element was recovered either by leaching the selectively roasted sulphide, or by direct fuming of GeS(I). Although these deposits have reportedly been depleted (2), new deposits of renierite have been discovered in Zaire. Alternative sources of germanium are therefore being sought worldwide for use in infrared optics, semiconductors, fibre optics, and catalysts. One such source is germanium-rich coal (2)."